Afiks Derivasional Pembentuk Nomina Deverbal Bahasa Arab dalam Buku Qira’atu ar-Rasyidah Jilid 1 - Azzahra, Shofannnisa Alifia; Wagiati, Wagiati; Kadir, Puspa Mirani (Universitas Muhammadiyah Gorontalo, 2024)
This research is purposed to find out how the process of derivational affixes forming Arabic deverbal nouns from the Qira'atu Ar-Rasyidah Volume 1 book and what grammatical meanings arise from it. The book is a textbook at the Gontor Islamic Boarding School and its affiliates which is unique either by the story plot or the grammar. Data collection focuses on 20 texts that are familiar to beginner-level students. The data were then analyzed using the distributional method supported by the ultimate constituent analysis technique. This research results presented with informal techniques. There are 31 data of derivational affixes forming deverbal nouns in the selected texts of this book. Derivational affixes that appear based on the letter of the formers include infixes marked with the letter ا /alif/, prefixes marked with the letter م /mim/, and confixes marked with م-ة /mim-ta marbutah/. These affixes give rise to new grammatical meanings of the original verb, namely subjective nouns (isim fa'il), masdar nouns (isim masdar), objective nouns (isim maf'ul), and locative nouns (isim makan).